Protective effects of diversified diets for dietary folate adequacy and serum homocysteine in breastfeeding mothers amid historic drought - Fujita, M.; Asthana, A.; Wamwere-Njoroge, George J. (Wiley, 2024)
Objectives The United Nations recommends that women consume ≥5 food groups, also known as the minimum dietary diversity score for women (MDD-W), for nutritional health. This is increasingly unattainable for populations in climate hot zones coping with food insecurity by prioritizing calories over dietary breadth. Breastfeeding mothers may be particularly vulnerable to adverse health impacts of low dietary diversity due to elevated nutritional requirements for lactation. We investigated how the protective effects of MDD-W for folate adequacy varies by MDD-W score and mother–infant life history characteristics.